On the topology of eigenfields - Arnold, Vladimir I. (Topological Methods in Nonlinear Analysis, 2005)
Topological properties of the eigenfields dependence on the eigenvalue positionis discussed for the cases, where the variety of the eigenfield vanishing does not divide the oscillating domain into pieces.